ANALISIS FAKTOR IMPLEMENTASI MANAJEMEN K3 TERHADAP KINERJA BIAYA PELAKSANAAN PROYEK KONSTRUKSI - Yaser Arafat (Lambung Mangkurat University Press, 2018)
The purpose of this study is to analyze the implementation of Occupational Health and Safety (OHS) that affect the cost performance of construction projects, and the relationship of OHS factors to the cost performance of construction implementation. The research design process begins with collecting primary data through a questionnaire. The main population for the questionnaire is the Construction Company in the South Kalimantan region, with a sample of 36 contracting companies. The instrument used was a closed questionnaire. The data analysis method of this study uses descriptive statistical analysis and correlation analysis. From the results of the study, the results obtained are firstly, the implementation of the OHS factor in this study proved to affect the cost performance. Making coordinated OHS planning is the most influential indicator on planning factors. OHS planning factor OHS is the factors that most influences cost performance, then the implementation and finally the evaluation factor. Secondly, OHS implementation factors that have a strong correlation to insurance cost performance are factors that monitor compliance with laws and regulations and other requirements related to the application of OHS in the workplace. Contract review is an indicator that is strongly related to project costs in terms of security equipment. The monitoring indicator of effectiveness of control is an indicator that has a strong correlation with health facilities. The evaluation indicator for the implementation of the company's OHS management system is an indicator that correlates very strongly to the cost of supervision of the application of safety. Indicators that have a strong correlation with the costs of accidents that occur are indicators of evaluating the effectiveness of OHS operations control. The indicator for conducting an OHS management system audit is an indicator that correlates very strongly with other costs associated with the work safety system.